ANÁLISE MEIÓTICA EM EXEMPLARES DE ABILA BOLIVARI GIGLIO-TOS, 1900 (ORTHOPTERA, ROMALEIDAE) DO MUNICÍPIO DE CAMPO GRANDE, MS. - Menezes Barbosa , Geovanna; Gonzalez Gouveia, Juceli; Maria de Rossi Vieira, Margarida (ANAIS DO ENIC, 2026)
-